The Developmental Trajectory of Teachers: A Theoretical Synthesis and Application to Counselor Education - Tangen, Jodi; Runcorn, Amy Qvammen; Hall, Brenda (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
Teaching is an important component of counselor education. However, there is a lack of literature exploring the developmental progress of counselor educators as teachers. In the following article, we review the research on doctoral-level teaching preparation in counselor education, present a synthesized model of teacher development informed from thirteen historic teacher developmental models, discuss our model in the context of counselor education, and provide limitations and recommendations for future research. Through this manuscript, counselor educators will learn the developmental trajectory of doctoral students and counselor educators. This will lead to a better understanding of the ways we facilitate and strengthen counselor educators development as teachers.